2004
DOI: 10.1038/sj.onc.1207362
|View full text |Cite
|
Sign up to set email alerts
|

Identification of alternatively spliced mRNA variants related to cancers by genome-wide ESTs alignment

Abstract: Several databases have been published to predict alternative splicing of mRNAs by analysing the exon linkage relationship by alignment of expressed sequence tags (ESTs) to the genome sequence; however, little effort has been made to investigate the relationship between cancers and alternative splicing. We developed a program, Alternative Splicing Assembler (ASA), to look for splicing variants of human gene transcripts by genome-wide ESTs alignment. Using ASA, we constructed the biosino alternative splicing dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
52
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 28 publications
3
52
0
Order By: Relevance
“…A recent analysis of more than 3 million transcripts in the EST database has demonstrated that 524 splice sites show statistically significant specificity to cancer tissues (57). These 524 cancer-specific splice sites derive from highly expressed splice isoforms, and many are being validated for use as reproducible molecular signatures of cancer (1,17). The TransExpress Cancer Human Splice Variant microarray (offered by ArrayIT, Sunnyvale, CA, as a test platform) includes 524 pairs of oligonucleotides optimized for splice variant profiling of these 524 genes.…”
Section: Resultsmentioning
confidence: 99%
“…A recent analysis of more than 3 million transcripts in the EST database has demonstrated that 524 splice sites show statistically significant specificity to cancer tissues (57). These 524 cancer-specific splice sites derive from highly expressed splice isoforms, and many are being validated for use as reproducible molecular signatures of cancer (1,17). The TransExpress Cancer Human Splice Variant microarray (offered by ArrayIT, Sunnyvale, CA, as a test platform) includes 524 pairs of oligonucleotides optimized for splice variant profiling of these 524 genes.…”
Section: Resultsmentioning
confidence: 99%
“…While the precise functional relevance of different spliced forms of specific transcripts has thus far been delineated in a limited number of cases, there is no question that alternative splicing yields variants with differential functions that are critical for development as well as for maintenance of normal cellular homeostasis and intercellular communication pathways (Matlin et al 2005). As such, it has also become evident that alterations in the regulation of splicing can have drastic consequences resulting in human diseases, including cancer (Xu and Lee 2003;Brinkman 2004;Hui et al 2004;Venables 2004;Relogio et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…When bioinformatic analysis was conducted for the investigation of alternative splicing, singleton EST sequences were considered to be insufficient data (Brett et al, 2000) because of the sequencing errors or genomic DNA contamination present in the EST database. However, singleton EST sequences could pro- vide enough evidence for transcript variants (Hui et al, 2004). On the basis of this report, the singleton EST was included in our analysis of cancer-specific transposable element fusion transcripts and database construction.…”
Section: Resultsmentioning
confidence: 99%
“…Several genes showed tumorspecific alternative splicing by integration of TEs (Okumura et al, 2005). In addition, genome-wide expressed sequence tag (EST) alignment indicated that alternatively spliced mRNA variants were related to various human cancers (Hui et al, 2004). Those transposable elements have been assumed to be noninfectious replication-defective retroviral fossils passed on during primate evolution.…”
Section: Introductionmentioning
confidence: 99%